Household Sharing and Commitment: Evidence from Panel Data on Individual Expenditures and Time Use - Lise, Jeremy; Yamada, Ken (Review of Economic Studies, 2019)
Abstract In this article, we analyse the dynamics of intra-household allocations using unique panel data on individual-specific consumption expenditures and time used for leisure, market production, and home production. Cross-sectional differences at the time of marriage in expected wage profiles between a husband and wife strongly affect the allocation of private consumption expenditures and time use by households in the cross section. There are substantial gender asymmetries in these allocations. Even for households where the husband and wife have identical wages, the private consumption expenditures for the wife are about half those for the husband. Within a given household over time, shocks to wages lead households to shift the relative weights in favour of the spouse receiving the favourable shock. Additionally, we find that households adjust the weights in response to large but not to small shocks; the adjustment to the weights is twice as large in the year leading up to a divorce; and adjustments are more frequent in dual- than in single-earner households. We interpret the data using a dynamic collective model of the household with potentially limited commitment.